Customer Billing Information System and Whatsapp Notification With Web-Based FCFS Method - Risandi Alfariz; Muhammad Revandi Ananda; Triase Triase (Sean Institute, 2026)
Digital transformation in the public service sector is now crucial to support work efficiency and effectiveness. At the Tirtanadi Water Company (PDAM) in North Sumatra, customer scheduling and billing activities are already carried out using an application, but still face several obstacles, such as the rarity of ordinary people to open the application to view their bills, resulting in many people experiencing delays in paying their bills, resulting in continued arrears and resulting in interest accruals. To address these challenges, a web-based information system was developed that implements the First Come First Serve (FCFS) scheduling algorithm. This algorithm functions to manage queues and schedules based on the order of incoming requests, resulting in a more structured and fair process. The implementation of this system is expected to increase efficiency in the billing process and support more responsive and accurate customer service within the PDAM.